Noon-Time Thermal Comfort in a Tropical, Hot-Humid Climate City in the Philippines - Velonta, Junelie Anthony; Martinez-Paglinawan, Kay Marie (Indonesian Journal of Earth Sciences, 2025)
Climate change and urbanization will rapidly increase land surface temperatures in cities with tropical, hot-humid climates. Understanding how this increase affects the individual human requires gauging current thermal comfort levels. This study uses the Modified Physiologically Equivalent Temperature (mPET) model to quantify noon-time thermal comfort within the Dumaguete city center. Twenty locations were investigated. These areas were organized based on the overhead cover in each location: Green Cover (GC) for locations with vegetation providing shade, Artificial Cover (AC) for locations with cover made of artificial or constructed materials, and Sparse Cover (SC) for areas with direct sun exposure. mPET calculated for both the GC and AC locations all fall below the 44.09°C limit for Moderate Heat Stress. However, most SC locations exceed said limit, indicating Strong Heat Stress. SC locations within urban canyons exhibited the highest mPET of all locations, corresponding to the highest heat stress levels. Wind velocity reduced mPET on all locations, affecting AC areas the most. Mean Radiant Temperature (Tmrt), which accounted for the heat radiated by the infrastructure around an area, had the greatest influence on mPET. This study has found that thermal comfort is greatly affected by the density of infrastructure surrounding a location. Specifically, tall buildings close to each other reflect and concentrate heat towards the ground level, greatly degrading thermal comfort for pedestrians. These results could help inform future zoning laws, encourage the use of vegetation as overhead cover for footpaths, and advocate urban designs which capitalize on wind to ventilate populous areas.